Oleic acid-based compounds as lube oil additives for engine oil - Rasha S. Kamal; Entsar E. Badr; Marwa R. Mishrif; Nour E.A. AbdEl-Sattar (Egyptian Journal of Petroleum)
The ongoing research focuses on preparing three compounds, based on oleic acid esters, through two steps to form 2-(3-acetylthioureido)-3-hydroxy-2-(hydroxymethyl) propyl oleate (Compound A), 2-(3-acetyl thioureido)-2-(hydroxymethyl) propane-1,3-diyl dioleate (Compound B) and 2-(3-acetyl thioureido)-2-[(oleoyloxy) methyl] propane-1,3-diyl dioleate (Compound C). The chemical structure of the prepared compounds has been distinguished and ascertained using different spectroscopic techniques as Fourier transform infrared spectroscopy (FTIR), proton and carbon nuclear magnetic resonance (1H and 13C NMR), quantum chemical study “theoretical studies”. The efficacy of the prepared compounds was ultimately scrutinized as lubricating oils’ additives. It gives excellent results as detergent/ dispersant additives. Both the experimental and theoretical quantum chemistry studies of antioxidant compounds yield insufficiently effective findings. The strength of the produced compounds shows that the one with three oleic groups is most effective when compared to one and two groups. Additionally, the dispersancy increases as the percentage of the dispersants rises from 0.25 to 1.5 %. Keep in mind that as time passes, dispersancy increases more. C > B > A, correspondingly, is the order in which the dispersancy percent decreases.